Study Protocol for an Ecological Momentary Assessment Study: TempRes “Temporal Variability of Risk and Resilience Factors for Suicidal Ideation” - Ernst, Mareike; Tibubos, Ana N.; Kubiak, Thomas; O'Connor, Rory C.; Beutel, Manfred E. (Frontiers in Psychiatry, 2022)
Suicide prevention is an important public mental health issue that can be significantly brought forward by recent advances in psychological research methods and assessment. The project “TempRes” aims to harness the power of Ecological Momentary Assessment (EMA) to investigate the transdiagnostic risk and resilience factors associated with suicidal ideation drawn from the most recent research in suicide prevention and personality assessment. Participants will comprise the general population (planned: N = 100) and a risk group (patients currently in psychosomatic or psychiatric treatment) (planned: N = 50). After a comprehensive baseline assessment, they will complete up to ten short assessments per day over the course of ten days at roughly equidistant intervals. In detail, the project examines the interplay of biography (previous suicidal behavior, experiences of childhood maltreatment), individual differences (level of personality functioning), and time-varying factors (entrapment, loneliness, mood) with respect to the emergence and fluctuation of suicidal ideation. There are two main research foci: First, the project will provide an operationalization and empirical verification of a core assumption of the integrated motivational-volitional model of suicide (IMV model). It will test whether the interaction of the time-varying predictors entrapment with loneliness (as a motivational moderator) explains reports of suicidal ideation over time. Second, it will be the first to examine personality functioning (a transdiagnostic, psychodynamically grounded conceptualization of vulnerability to psychological crises over the life span) as a time-invariant predictor of suicidal ideation assessed within an intensive longitudinal study design. The main analyses will be built on linear mixed models. The overarching aim of the project is to gain a better understanding of the psychological dynamics underlying suicidal ideation in different populations by bringing together concepts from different theoretical traditions. This will inform prevention efforts geared towards the general public as well as intervention in clinical populations.